Clinical evaluation and role of patch testing in identifying the exogenous causes in patients presenting with hand eczema - Jyothi Lakshmi, S.; Gopalakrishnan, K. (International Journal of Research in Dermatology, 2019)
Background: Hand eczema is a common dermatological problem resulting from both allergic and irritant contactants. Patch testing helps in both diagnosing and identifying allergens. Methods: A cross sectional study wherein 110 patients with hand eczema attending Dermatology OPD were included and patch testing was done. Data was collected from April 2015 to July 2016 and was analysed for clinical and epidemiological characteristics. Results: The mean age of the patients studied was 40.27 years with male preponderance. Housewives were the major occupational group comprising 25.5% followed by masons 21.8% and farmers 10.9%. The commonest morphological type was hyperkeratotic type constituting 51.85%, followed by fingertip eczema 19.1%, discoid eczema 11.8%, wear and tear dermatitis 8.2%, recurrent focal palmar peeling 4.5% and pompholyx 4.5%. In the study group 60% of patients showed positive patch test result. A total 66 patients showed patch test positivity to a total of 69 allergens. Nickel was the most common allergen 27.3% identified followed by potassium dichromate 10.9%. Among female patients with positive patch test 70% reacted to nickel and similarly 83.5% of male patients reacted to potassium dichromate. Parthenium allergy was seen in 41.5% of farmers studied. Conclusions: Patch testing has a definitive role in diagnosing hand eczema caused by allergens. Identifying the allergen involved helps the clinician in advising the patient regarding further avoidance of contactants.